Reimagining businesses with AI - Sinha, Sudhi, 1975-; Huraimel, Khaled Al, 1974- (Hoboken : John Wiley & Sons, Inc., 2020)
Discover what AI can do for your business with this approachable and comprehensive resource Reimagining Businesses with AI acquaints readers with both the business challenges and opportunities presented by the rapid growth and progress of artificial intelligence. The accomplished authors and digital executives of the book provide you with a multi-industry approach to understanding the intersection of AI and business. The book walks you through the process of recognizing and capitalizing on AI's potential for your own business. The authors describe: How to build a technological foundation that allows for the rapid implementation of artificial intelligence How to manage the disruptive nature of powerful technology while simultaneously harnessing its capabilities The ethical implications and security and privacy concerns raised by the spread of AI Perfect for business executives and managers who seek a jargon-free and approachable manual on how to implement artificial intelligence in everyday operations, Reimagining Businesses with AI also belongs on the bookshelves of anyone curious about the interaction between artificial intelligence and business.
Acknowledgments ; Chapter 1: Introduction ; Chapter 2: Building a Framework for Applying AI ; Chapter 3: Transforming Healthcare with AI ; Chapter 4: Transforming Education with AI ; Chapter 5: Transforming Transportation with AI ; Chapter 6: Transforming Retail with AI ; Chapter 7: Transforming Financial Services with AI ; Chapter 8: Transforming the Built Environment with AI ; Chapter 9: Transforming Smart Cities with AI ; Chapter 10: Transforming Government and Citizen Services with AI ; Chapter 11: Building the Right Technology Landscape ; Chapter 12: Dealing with Ethics, Privacy, and Security ; Chapter 13: Building the Partner Ecosystem for AI-driven Transformation ; Chapter 14: Building Winning Teams for AI-Driven Transformation ; Chapter 15: Managing Change for AI-Driven Transformation ; Index
Description based on CIP data; resource not viewed.
John Wiley and Sons
Keywords: Artificial intelligence -- Economic aspects; Information technology -- Management; Organizational learning; Organizational change; Organizational Innovation; Intelligence artificielle; Technologie de l'information -- Gestion; Apprentissage organisationnel; Changement organisationnel; Artificial intelligence -- Economic aspects; Information technology -- Management; Organizational change; Organizational learning